THE QUALITY IMPROVEMENT OF PUBLIC SERVICE THROUGH A BILINGUAL APPROACH - Muhammad Taupik (stiatabalong.ac.id, 2022)
This article intends to describe how to increase the quality of public services with a bilingual approach. Favorable public service is a service that is carried out quickly, on time, correctly, and pleasantly. The quality of public services is a characteristic of public services that are expected to meet the needs of users. In order to face the industrial era 4.0. Where public service employees are required to develop themselves in order to be able to compete. Public services with a bilingual approach are services that utilize the use of two languages, Indonesian and English, in all service activities in a balanced manner. Provision of funds, and commitments. Keyword: Public service, service quality, and bilingual approach